2012 Spillover Report. (Policy Papers; Policy Paper, 2012)
Spillover reports examine the external effects of domestic policies in five systemic economies (S5), comprising China, the Euro Area, Japan, the United Kingdom, and the United States. The report aims to provide an added perspective to the policy line developed in the Article IV discussions with these entities and an input into the Fund's broader multilateral surveillance. Topics for this report were chosen based on consultations with officials from the S5 and selected emerging markets (Brazil, the Czech Republic, India, Korea, Mexico, Poland, Russia, Saudi Arabia, Singapore, South Africa, and Turkey). Each participant was asked about policy concerns and spillovers from the S5. To facilitate candor, the report does not attribute views regarding partner countries. Rather than try to capture the full range of spillovers, this report builds on last year's findings, focusing on the forward-looking issues raised by partners and on S5 officials' reactions.